Potential Hazards of Erosion and Conservation Strategis in the Sail Sub-Watershed, Pekanbaru City, Riau Province, Indonesia - Ramsof, Rani Amalia; Zakaria, Zufialdi; Irvan Sophian; Arie Afriadi (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Erosion in watershed area can be triggered by changes in land use, human activities, and cause increased sedimentation, flood risk, and environmental degradation, effective conservation measures are necessary to ensure its impact is reduced. To determine potential erosion hazards in Sail Sub-Watershed the method used is Revised Universal Soil Loss Equation (RUSLE), parameters include rainfall, soil erodibility, slope length and slope, and land cover and soil conservation. In addition, an analysis of permissible erosion and an erosion hazard index were carried out. The research results show that the level of erosion hazard is influenced by the value of the rain erosivity factor (R) of 2678.98 m with the wet rainfall classification. The soil erodibility factor (K) is dominated by cambisol soil types with a K value of 0.28 and podzolic with a K value of 0.20. The length and slope (LS) factors are dominated by flat topography with an LS value of 0.4. Meanwhile, the land cover and soil conservation (CP) factors mostly consist of open land, shrubs and plantations that have not received any conservation efforts. The erosion hazard level (TBE) in  ranges from moderate to very severe, indicating that the areas affected by erosion are predominantly due to the use of open land, such as at station 16. The erosion hazard index (EHI) varies from moderate to very high. As a land conservation effort, vegetative methods in the form of reforestation are recommended for open land, while terrace walls or wet masonry are recommended for agricultural land and plantations. In addition, conservation structures such as retaining walls, bench terraces, or stairs can be implemented on plantation land to reduce the danger of erosion.